1983
DOI: 10.1115/1.3254526
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Molecular Rarefaction Effects in Gas Lubricated Bearings at Ultra-Low Clearances

Abstract: The experimental investigation discussed here gives experimental confirmation of the slip-flow theory for modeling hydrodynamic gas bearings with clearances below 0.25 microns. An interferometric technique employing two CW lasers is used to measure the small clearances with an accuracy of 0.025 microns. The effects of molecular rarefaction are studied by operating the slider bearing in different gas media of different mean free paths. Bearings operating at extremely high local Knudsen numbers are studied witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
150
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(153 citation statements)
references
References 0 publications
3
150
0
Order By: Relevance
“…Table 1 presents a comparison of the theoretical values of A 1 and A 2 that have been proposed in the literature [9,22,31,[36][37][38][39]. It can be seen that as yet, no agreement has been reached on the correct value of the second-order coefficient.…”
Section: Analytical Models: Second-order Formulationsmentioning
confidence: 95%
“…Table 1 presents a comparison of the theoretical values of A 1 and A 2 that have been proposed in the literature [9,22,31,[36][37][38][39]. It can be seen that as yet, no agreement has been reached on the correct value of the second-order coefficient.…”
Section: Analytical Models: Second-order Formulationsmentioning
confidence: 95%
“…A gas lubricated inclined plane slider bearing has been examined by Burgdofer (1959) in the slip flow regime using a first-order slip model with the boundary slip velocity given at a mean free path distance from the wall. Hsia & Domoto (1983) incorporated a second-order slip model and Mitsuya (1993) developed a modified second-order slip model through additional physical considerations, referred to as a 1.5-order slip model. Slip effects in a journal bearing were investigated using a first-order model for compressible flow by Malik (1984) and for incompressible flow by Maureau (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, in order to model rarefaction effects in ultra-thin film lubrication, various velocity-slip models have been incorporated into the NS equations for a variety of bearing geometries. [10][11][12][13][14] However, the experiments [15][16][17][18] have shown that the modified Reynolds equations underpredict the pressure rise when the gas thickness is below 250 nm. 1 Recently, a new extended Reynolds equation based on the regularized 13 moment equations and the lubrication theory has been derived for gas slider bearings, but it can only be applied for the Knudsen number up to unity.…”
Section: Introductionmentioning
confidence: 99%